2016
DOI: 10.1007/s12040-016-0674-1
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis, zircon U–Pb age, and geochemistry of the A-type Mogou syenite, western Henan Province: Implications for Mesozoic tectono-magmatic evolution of the Qinling Orogen

Abstract: The Mogou syenite intruded into the Mesoproterozoic Xiong'er Group is the main lithostratigraphic unit, along the southern margin of the North China Craton (NCC). This paper reports zircon LA-ICP-MS data, whole-rock major and trace element compositions of late Triassic magmatic rocks in the Mogou syenite, in order to constrain the formation age of the Mogou syenite, research the origin and evolution of the magma and analyse the geodynamic setting of the Qinling Orogen (QO) in Late Triassic. These rocks consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…The Proterozoic-Paleozoic subduction of the Shangdan oceanic crust Dong et al, 2011;Yang et al, 2003) and Mesozoic subduction of the Izanagi plate Liu, Gurnis, Ma, & Zhang, 2017) beneath the NCC could both contribute to the metasomatism of the NCC (Xu, Zheng, & Zhao, 2011b;Yang, Teng, Zhang, & Li, 2012;Li, 2015;Song et al, 2016). The presence of a metasomatized lithospheric mantle beneath the southern margin of the NCC has also been supported by the emplacement of many intrusions, including the 245-210 Ma Mogou alkali pluton Lu, Liang, Bai, & Lu, 2013;He et al, 2016), the 225-209 Ma Huangshuian and Huanglongpu carbonatites (Stein et al, 1997;Huang, Wu, Du, & He, 1994;Huang, Hou, Yang, Li, & Xu, 2009;Du et al, 2004;Xu et al, 2011a;Cao et al, 2014;Song et al, 2015Song et al, , 2016, the ca.160 Ma Xinyang peridotitic xenolithos (Zheng, Sun, Zhou, & Robinson, 2005, Zheng et al, 2008; enriched by South China), the 129 Ma Huanglongpu diabase dikes (Zhao, Mao, Ye, Xie, & Yang, 2010), and the 122 Ma Tianqiaogou monzodiorites (Gao, Zhao, Bao, & Yang, 2014).…”
Section: Sources Of Telluriummentioning
confidence: 99%
“…The Proterozoic-Paleozoic subduction of the Shangdan oceanic crust Dong et al, 2011;Yang et al, 2003) and Mesozoic subduction of the Izanagi plate Liu, Gurnis, Ma, & Zhang, 2017) beneath the NCC could both contribute to the metasomatism of the NCC (Xu, Zheng, & Zhao, 2011b;Yang, Teng, Zhang, & Li, 2012;Li, 2015;Song et al, 2016). The presence of a metasomatized lithospheric mantle beneath the southern margin of the NCC has also been supported by the emplacement of many intrusions, including the 245-210 Ma Mogou alkali pluton Lu, Liang, Bai, & Lu, 2013;He et al, 2016), the 225-209 Ma Huangshuian and Huanglongpu carbonatites (Stein et al, 1997;Huang, Wu, Du, & He, 1994;Huang, Hou, Yang, Li, & Xu, 2009;Du et al, 2004;Xu et al, 2011a;Cao et al, 2014;Song et al, 2015Song et al, , 2016, the ca.160 Ma Xinyang peridotitic xenolithos (Zheng, Sun, Zhou, & Robinson, 2005, Zheng et al, 2008; enriched by South China), the 129 Ma Huanglongpu diabase dikes (Zhao, Mao, Ye, Xie, & Yang, 2010), and the 122 Ma Tianqiaogou monzodiorites (Gao, Zhao, Bao, & Yang, 2014).…”
Section: Sources Of Telluriummentioning
confidence: 99%
“…LA–ICP–MS U–Pb analyses on zircon grains indicate that the Mogou pluton was emplaced between 245.5 ± 8.0 and 210.4 ± 2.0 Ma (J. Cao, Ye, Li, Zhang, et al, ; X. He et al, ; R. Lu, Liang, Bai, & Lu, ). X.…”
Section: Geological Settingmentioning
confidence: 99%
“…X. He et al () proposed that the Mogou syenite records a transition period from compression to extension at ~227 Ma. J. Cao, Ye, Li, Zhang, et al () suggested that the early phase of the Mogou pluton was formed in a local extensional setting during the collision process, and the late phase was emplaced in a post‐collision setting.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations